The Experience of the Tourist in a Technologically-Driven Age: A Continuum Between the Tourist Guide and Technology - Michelle De La Harpe; Karina Sevenhuysen (Journal of Tourismology)
The aim of this paper is to examine how new technologies shape the experience of the tourist. This is to further the understanding of tourism’s place in a technologically-driven age. The methodology of the study includes an analysis, comparison and evaluation of elements and factors involved in contributing to a quality tourist experience. The experience of the tourist is a personal and individualistic occurrence and can be improved with the help of both new technologies and the tourist guide. The finding that is made is that both the personal touch of the tourist guide as well as the interactive features of technology have a place in the provision of quality tourism experiences. This in turn implies that both tourist guides and new technologies should be included in the tourism experience. Only then can a quality tourism experience be provided for the 21st century tourist. There are many papers examining the experience of the tourist. However, few have looked at the implications of the development of new technologies on the experience of the tourist. This article suggests a scale on which the tourist experience can be based on, in relation to both tourist guides and new technologies.